Energy analysis of sugarcane bagasse after enzymatic catalysis process - de Morais, Leandro Cardoso [UNESP]; Maia, Amanda Alves Domingos [UNESP]; Yamaji, Fábio Minoru; Viana, Sthefany Rodrigues Fernandes [UNESP]; Resende, Pedro (Springer Nature, 2020)
Nowadays, countries produce approximately 1700 million tons of sugarcane per year. However, many countries now find it difficult to produce sufficient energy, generating a relevant socioeconomic impact. The objective of this work is to study the potential energy of sugarcane bagasse after decomposing fungus process. This fungus, the basidiomycete Pleurotus ostreatus, acts in the bioconversion of lignocellulosic residues, through the decomposition of the solid substrate in a process of enzymatic catalysis. The activation energy, Ea, varied from 12 to 145 kJ/mol, and the calorific value and the fixed carbon obtained were 21 MJ/kg and 82.4%, respectively, values considered acceptable for a solid biofuel. In the results of the enzymatic analysis performed through the laccase secretion and manganese peroxidase (MnP), measured by the Fourier transform infrared spectroscopy technique (FT-IR), it is possible to identify when there was degradation of the lignin due to the methoxy group (CH3) elongation. Scanning electron microscope (SEM) analysis showed partially fragmented structures, which occurred due to catalysis and pyrolysis processes, respectively. [Figure not available: see fulltext.].
Keywords: Bioconversion; Pleurotus ostreatus; Solid biofuel; Sugarcane bagasse waste; White-rot fungi